Strategy for Strengthening Legal Protection for Corruption Victims as a Manifestation of the Principle of Sustainable Social Justice - Sunggu, Eben Patar Op; Riswadi, Riswadi (Indonesian Journal of Multidisciplinary Science, 2025)
Yet, under the principle of social justice, victims of crimes—including corruption—are entitled to fair and sustainable recovery. This study aims to analyze the role of law in upholding social justice for victims of corruption by examining the available rehabilitation mechanisms within Indonesia’s legal framework. It also explores the regulatory limitations and challenges in implementing legal protection for corruption victims. This research employs a normative juridical method, utilizing both a statute approach and a conceptual approach. The statute approach involves an analysis of various regulations related to corruption and victim protection, For example, Law No. 13 of 2006 in connection with Law No. 31 of 2014 on the Protection of Witnesses and Victims, and Law No. 31 of 1999 in connection with Law No. 20 of 2001 on the Eradication of Corruption Crimes. In the meantime, the conceptual approach investigates social justice themes such as restitution that are connected to the restoration of the rights of victims of corruption, compensation, and rehabilitation as recognized in both national and international law. The results of this study are expected to contribute to the development of legal policies that are more victim-oriented and to strengthen the implementation of social justice within the criminal justice system. With effective legal mechanisms in place, it is hoped that the recovery of corruption victims can be optimized as part of a more comprehensive anti-corruption strategy.